Green fabrication of lanthanide-doped hydroxide-based phosphors: Y(OH)3:Eu3+ nanoparticles for white light generation - Guner, Tugrul; Kus, Anilcan; Ozcan, Mehmet; Genc, Aziz; Sahin, Hasan; Demir, Mustafa M. (Beilstein Journal of Nanotechnology, 2019)
Phosphors can serve as color conversion layers to generate white light with varying optical features, including color rendering index (CRI), high correlated color temperature (CCT), and luminous efficacy. However, they are typically produced under harsh synthesis conditions such as high temperature, high pressure, and/or by employing a large amount of solvent. In this work, a facile, water-based, rapid method has been proposed to fabricate lanthanide-doped hydroxide-based phosphors. In this sense, sub-micrometer-sized Y(OH)3:Eu3+ particles (as red phosphor) were synthesized in water at ambient conditions in ≤60 min reaction time. The doping ratio was controlled from 2.5–20 mol %. Additionally, first principle calculations were performed on Y(OH)3:Eu3+ to understand the preferable doping scenario and its optoelectronic properties. As an application, these fabricated red phosphors were integrated into a PDMS/YAG:Ce3+ composite and used to generate white light. The resulting white light showed a remarkable improvement (≈24%) in terms of luminous efficiency, a slight reduction of CCT (from 3900 to 3600 K), and an unchanged CRI (≈60) as the amount of Y(OH)3:Eu3+ was increased.
Keywords: green synthesis; phosphors; phosphor-converted white LED; white LED; white light generation

(untitled) - Tan, S. T.; Sun, X. W.; Demir, H. V.; DenBaars, S. P. (IEEE Photonics J., 2012)

(untitled) - Schubert, E. F.; Kim, J. K. (Science, 2005)

(untitled) - Shur, M. S.; Zukauskas, R. (Proc. IEEE, 2005)

(untitled) - Tsao, J. Y.; Saunders, H. D.; Creighton, J. R.; Coltrin, M. E.; Simmons, J. A. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Schubert, E. F.; Kim, J. K.; Luo, H.; Xi, J.-Q. (Rep. Prog. Phys., 2006)

(untitled) - Cho, J.; Park, J. H.; Kim, J. K.; Schubert, E. F. (Laser Photonics Rev., 2017)

(untitled) - Qin, X.; Liu, X.; Huang, W.; Bettinelli, M.; Liu, X. (Chem. Rev., 2017)

(untitled) - Wang, L.; Xie, R.-J.; Suehiro, T.; Takeda, T.; Hirosaki, N. (Chem. Rev., 2018)

(untitled) - Xia, Z.; Xu, Z.; Chen, M.; Liu, Q. (Dalton Trans., 2016)

(untitled) - Ye, S.; Xiao, F.; Pan, Y. X.; Ma, Y. Y.; Zhang, Q. Y. (Mater. Sci. Eng., R, 2010)

(untitled) - George, N. C.; Denault, K. A.; Seshadri, R. (Annu. Rev. Mater. Res., 2013)

(untitled) - Shinde, K. N.; Dhoble, S. J. (Crit. Rev. Solid State Mater. Sci., 2014)

(untitled) - Lin, C. C.; Liu, R.-S. (J. Phys. Chem. Lett., 2011)

(untitled) - Güner, T.; Köseoğlu, D.; Demir, M. M. (Opt. Mater., 2016)

(untitled) - Güner, T.; Şentürk, U.; Demir, M. M. (Opt. Mater., 2017)

(untitled) - Narendran, N.; Gu, Y.; Freyssinier-Nova, J. P.; Zhu, Y. (Phys. Status Solidi A, 2005)

(untitled) - Allen, S. C.; Steckl, A. J. (Appl. Phys. Lett., 2008)

(untitled) - Shen, X.; Zhang, D.-F.; Fan, X.-W.; Hu, G.-S.; Bian, X.-B.; Yang, L. (J. Mater. Sci.: Mater. Electron., 2016)

(untitled) - Saladino, M. L.; Chillura Martino, D.; Floriano, M. A.; Hreniak, D.; Marciniak, L.; Stręk, W.; Caponetti, E. (J. Phys. Chem. C, 2014)

(untitled) - Li, J.; Yan, J.; Wen, D.; Khan, W. U.; Shi, J.; Wu, M.; Su, Q.; Tanner, P. A. (J. Mater. Chem. C, 2016)

(untitled) - Lin, C. C.; Meijerink, A.; Liu, R.-S. (J. Phys. Chem. Lett., 2016)

(untitled) - Jang, E.; Jun, S.; Jang, H.; Lim, J.; Kim, B.; Kim, Y. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Guner, T.; Demir, M. M. (Phys. Status Solidi A, 2018)

(untitled) - Guner, T.; Aksoy, E.; Demir, M. M.; Varlikli, C. (Dyes Pigm., 2019)

(untitled) - Dorenbos, P. (J. Lumin., 2003)

(untitled) - Verma, T.; Agrawal, S. (J. Fluoresc., 2018)

(untitled) - Atabaev, T. S.; Hwang, Y.-H.; Kim, H.-K. (Nanoscale Res. Lett., 2012)

(untitled) - Lee, S.-H.; Choi, J. I.; Kim, Y. J.; Han, J. K.; Ha, J.; Novitskaya, E.; Talbot, J. B.; McKittrick, J. (Mater. Charact., 2015)

(untitled) - Tissue, B. M.; Yuan, H. B. (J. Solid State Chem., 2003)

(untitled) - Saravanan, T.; Raj, S. G.; Chandar, N. R. K.; Jayavel, R. (J. Nanosci. Nanotechnol., 2015)

(untitled) - Li, N.; Yanagisawa, K. (J. Solid State Chem., 2008)

(untitled) - Higashi, K.; Watanabe, Y.; Iso, Y.; Isobe, T. (RSC Adv., 2017)

(untitled) - Towata, A.; Sivakumar, M.; Yasui, K.; Tuziuti, T.; Kozuka, T.; Iida, Y. (J. Mater. Sci., 2008)

(untitled) - Shiba, F.; Tamagawa, T.; Kojima, T.; Okawa, Y. (CrystEngComm, 2013)

(untitled) - Darr, J. A.; Zhang, J.; Makwana, N. M.; Weng, X. (Chem. Rev., 2017)

(untitled) - Li, D.; Wang, Y.; Zhang, X.; Dong, H.; Liu, L.; Shi, G.; Song, Y. (J. Appl. Phys., 2012)

(untitled) - Bai, Y.; Wang, Y.; Peng, G.; Yang, K.; Zhang, X.; Song, Y. (J. Alloys Compd., 2009)

(untitled) - Dubey, A.; Soni, A. K.; Kumari, A.; Dey, R.; Rai, V. K. (J. Alloys Compd., 2017)

(untitled) - Zhao, C.; Kong, X.; Liu, X.; Tu, L.; Wu, F.; Zhang, Y.; Liu, K.; Zeng, Q.; Zhang, H. (Nanoscale, 2013)

(untitled) - Wu, Y.; Sun, W.; Zhou, X.; Jiao, X.; Ding, J.; Li, Y. (J. Rare Earths, 2009)

(untitled) - Li, N.; Yanagisawa, K.; Kumada, N. (Cryst. Growth Des., 2009)

(untitled) - Wu, X.; Tao, Y.; Gao, F.; Dong, L.; Hu, Z. (J. Cryst. Growth, 2005)

(untitled) - Zhang, X.-M.; Huang, M.-L.; Zhang, Z.-J.; Liu, B.-Q.; Zhao, J.-T. (Mater. Lett., 2012)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B, 1999)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1993)

(untitled) - Kresse, G.; Furthmüller, J.; Hafner, J. (Europhys. Lett., 1995)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Henkelman, G.; Arnaldsson, A.; Jónsson, H. (Comput. Mater. Sci., 2006)

(untitled) - Srinivasan, R.; Yogamalar, N. R.; Elanchezhiyan, J.; Joseyphus, R. J.; Bose, A. C. (J. Alloys Compd., 2010)

(untitled) - Popovici, E.-J.; Muresan, L.; Amalia, H.; Indrea, E.; Vasilescu, M. (J. Alloys Compd., 2007)

(untitled) - Hussain, S. K.; Nagaraju, G.; Pavitra, E.; Seeta Rama Raju, G.; Yu, J. S. (CrystEngComm, 2015)

(untitled) - Toshima, T.; Ishikawa, H.; Tanda, S.; Akiyama, T. (Cryst. Growth Des., 2008)

(untitled) - Liu, Q.; Zhou, Y.; Tian, Z.; Chen, X.; Gao, J.; Zou, Z. (J. Mater. Chem., 2012)

(untitled) - Xia, B.; Xiao, S.-J.; Wang, J.; Guo, D.-J. (Thin Solid Films, 2005)